KESIAPAN MADRASAH IBTIDAIYAH DALAM MENGHADAPI IMPLEMENTASI KURIKULUM MERDEKA - Masnun, Moh (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The implementation of the Independent Curriculum is a big step in advancing education in Indonesia. Through the Independent Curriculum, it is hoped that it can improve the quality and relevance of education in facing the times. Although many public schools under the Ministry of Religion have implemented the Independent Curriculum, implementation in madrasas is still not intensive. This study used a descriptive qualitative research method which was conducted on the madrasah head, deputy head of curriculum, and 28 representative teachers from each Madrasah Ibtidaiyah Cirebon City for the 2022/2023 academic year. Data was collected by distributing questionnaires and interviews. The results showed that madrasa readiness in facing the implementation of the Independent Curriculum was quite good, with three aspects of readiness: learning planning with sufficient criteria, the learning process with sufficient criteria, and the assessment process with insufficient criteria. The conclusion is that several Islamic Elementary Schools in Cirebon City which are included in the study have sufficient readiness to face the implementation of the independent curriculum, where readiness includes readiness to plan lessons, and carry out learning.